A Conflict Avoidance Scheme for WiMedia Wireless Home Networks. (28th March 2013) - Hur, Kyeong; Sohn, Won-Sung; Lee, YangSun
Abstract : We propose an efficient resource reservation scheme for UWB (Ultrawideband) WPAN (Wireless Personal Area Network) with D-MAC (Distributed Medium Access Control). Since the WiMedia D-MAC supporting DRP (Distributed Reservation Protocol) scheme causes lots of conflicts due to failure of beacon detection in wireless channel environment, overall performances of the WiMedia D-MAC can be deteriorated. Therefore, we propose Relay DRP protocol, which makes a relay path to avoid DRP conflicts or harsh channel conditions through cooperative relay transmission scheme and is compliant with the current WiMedia D-MAC protocol. Simulation results demonstrate performance improvements of the proposed method for throughput and energy consumption.